In Situ Generation of Ultrathin MoS2 Nanosheets in Carbon Matrix for High Energy Density Photo‐Responsive Supercapacitors. Issue 24 (7th July 2022) - Tang, Zhenbin; Dai, Juguo; Wei, Wenkang; Gao, Zhi; Liang, Zhixuan; Wu, Chenzhi; Zeng, Birong; Xu, Yiting; Chen, Guorong; Luo, Weiang; Yuan, Conghui; Dai, Lizong
Abstract: Stimuli‐responsive supercapacitors have attracted broad interest in constructing self‐powered smart devices. However, due to the demand for high cyclic stability, supercapacitors usually utilize stable or inert electrode materials, which are difficult to exhibit dynamic or stimuli‐responsive behavior. Herein, this issue is addressed by designing a MoS2 @carbon core‐shell structure with ultrathin MoS2 nanosheets incorporated in the carbon matrix. In the three‐electrode system, MoS2 @carbon delivers a specific capacitance of 1302 F g −1 at a current density of 1.0 A g −1 and shows a 90% capacitance retention after 10 000 charging‐discharging cycles. The MoS2 @carbon‐based asymmetric supercapacitor displays an energy density of 75.1 Wh kg −1 at the power density of 900 W kg −1 . Because the photo‐generated electrons can efficiently migrate from MoS2 nanosheets to the carbon matrix, the assembled photo‐responsive supercapacitor can answer the stimulation of ultraviolet‐visible‐near infrared illumination by increasing the capacitance. Particularly, under the stimulation of UV light (365 nm, 0.08 W cm −2 ), the device exhibits a ≈4.50% (≈13.9 F g −1 ) increase in capacitance after each charging‐discharging cycle. The study provides a guideline for designing multi‐functional supercapacitors that serve as both the energy supplier and the photo‐detector. Abstract : An in situ approach based on the coordination between boronate ester polymers and metal ions has been developed to generate ultrathin MoS2 nanosheets in the carbon matrix, affording MoS2 @carbon core‐shell particles. Due to the synergistic effect between the semiconductor MoS2 and the multi‐element co‐doped carbon matrix, MoS2 @carbon exhibits outstanding capacitive performance and light‐triggered reversible capacitance evolution.